Ireland : Financial System Stability Assessment Update. (IMF Staff Country Reports; Country Report ;, 2006)
The Irish financial sector has continued to perform well since its participation in the Financial Sector Assessment Program (FSAP) in 2000. Although the outlook remains very strong for 2006-07, there are some macroeconomic risks that could have implications for the financial system asset quality. The financial system seems well placed to absorb the impact of a downturn in either house prices or growth more generally. Further, good progress has been achieved since the 2000 FSAP in strengthening the regulatory and supervisory framework.